Multicenter real-world data on immunotherapy for R/M HNSCC from China: comprehensive analysis of efficacy and survival differences across diverse clinical backgrounds, and identification of predictive peripheral blood biomarkers - Sun, Feifan; Pu, Shasha; Hou, Bingxin; Liu, Jingyi; Liu, Changhao; Zang, Jian; Su, Haichuan; Wang, Zhongwei; Song, Xuejiao; Wang, Siyu; Jiang, Dongbo; Zhao, Lina; et al. (Frontiers in Immunology, 2026)
BackgroundPD-1 inhibitors are first-line treatments for recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC). However, previous trials included few participants from mainland China and other Asian regions and differed from real-world practice. PD-L1 expression alone has limited predictive value. This study aimed to systematically evaluate efficacy and survival differences in diverse clinical scenarios and identify associated peripheral blood markers (PBMs).MethodsData were retrospectively collected from 105 R/M HNSCC patients treated with first-line immunotherapy alone or in combination across 3 hospitals in China (2020.01-2022.12). Primary endpoints were overall survival (OS) and progression-free survival (PFS). We assessed efficacy, survival, and safety, and developed predictive models. Data analyses were performed using SPSS 26.0 and GraphPad Prism 8.0.1.ResultsThe median follow-up was 21 months. The objective response rate was 37.14%. Median OS was 21 months (1-year OS: 81.02%), and median PFS was 11 months (1-year PFS: 39.47%). Immunotherapy was more effective for distant metastasis (DM) than local recurrence (LR). For patients with LR, DM, or both, median PFS was 12, 14, and 7.5 months, respectively (P = 0.0029). Higher combined positive score (CPS) predicted better outcomes. Median OS for CPS ≥ 20, 1 ≤ CPS < 20, and CPS < 1 was 32, 20, and 12 months, respectively (P = 0.0008). In the comparison of combination versus single-agent immunotherapy, median PFS was 12 versus 9 months (P = 0.0044). Combining taxanes with immunotherapy yielded favorable results, with a median OS of 27 months. No survival difference was found between domestic and imported PD-1 inhibitors. Secondary radiotherapy did not improve survival. Increased peripheral blood lymphocyte subsets and decreased peripheral blood inflammatory markers were associated with superior immunotherapy outcomes. Key predictive PBMs included baseline CD8+ T cells, CD3+ T cells at 12 weeks post-treatment (12w pt), CD4+ T cells at 6w pt, and CD8+ T cells at 12w pt.ConclusionThis study focused on evaluating immunotherapy efficacy and survival differences in R/M HNSCC patients across various clinical background. Dynamic PBMs correlated closely with immunotherapy response and survival prognosis. These findings expanded treatment options and supported personalized decisions. R/M HNSCC, Immunotherapy, Real-world study, Efficacy and survival differences, Predictive markers.